Evaluating The effectiveness of social media strategies in branding halal tourism: The case of Banyuwangi Indonesia - Dinta Kharisma Almeira; Surwandono Surwandono; Ahmad Yusuf Syaefullah; Syahera Nursita Azzahra (Nur Science Institute, 2026)
Halal Tourism has become one of the rapidly growing trends in the global tourism industry. In this digital era, social media plays a crucial role in promotion. This article analyzes YouTube and TikTok users’ responses to Halal Tourism branding in Banyuwangi in 2024, examining views, likes, comments, and comment sentiment. Using a descriptive-analytical qualitative approach and the concept of Halal Tourism Branding, the study compares user interactions across both platforms. The findings show that TikTok is accessed and preferred more frequently, while YouTube offers deeper user engagement. TikTok users also tend give more positive feedback on specific aspects compared to YouTube users. These results suggest that Halal Tourism marketing in Banyuwangi should be tailored to the unique strengths and audience behavior of each platform, ensuring more effective outreach and sustainable destination branding strategies. This approach also encourages interest and trust.